Association between disease severity and systemic inflammation in patients with dilated cardiomyopathy - Abdullayev , Timur; Rakhmatov , Mahmud; Gulomov , Khumoyun (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. The aim of this study was to investigate the relationship between clinical-hemodynamic parameters and inflammatory markers (C-reactive protein, interleukin-6, tumor necrosis factor-α) in patients with dilated cardiomyopathy.Materials and methods. The study included 42 patients (mean age 38.5±1.2 years) with dilated cardiomyopathy and chronic heart failure classified as NYHA functional class II–IV. The patients were divided into two groups: Group I – class II (n=12) and Group II – class III–IV (n=30).Results. As heart failure severity increased (class III–IV), serum levels of C-reactive protein (7.6±1.1 mg/L vs. 4.1±0.6 mg/L, p